Slum Upgrading and Changes in the Welfare of Home-Based Entrepreneurs in Kampung Bahari Tambaklorok, Indonesia - Tyas, Wido Prananing; Damayanti, Maya; Hutama, Julius Kevin Putra; Rachma, Renesia (Department of Urban and Regional Planning, Universitas Diponegoro, 2022)
This study examines changes in community welfare, especially among home-based entrepreneurs in Kampung Bahari Tambaklorok, Semarang, Indonesia. This study hypothesizes that after planning the development of Kampung Bahari Tambaklorok as a tourist destination for five out of twenty years, there has been a change in the socio-economic welfare conditions of the community, primarily home-based enterprise actors. Research data were obtained through observations, questionnaires, and interviews. In addition, this study conducted a descriptive analysis, scoring, and Likert Scale to obtain an overview of changes in socio-economic conditions based on community perceptions. These two analyses examine the changes in welfare experienced by the Tambaklorok community, especially home-based entrepreneurs. Thus, it may impact the sustainability of development planning for the Kampung Bahari Tambaklorok Semarang. However, the result of this study is that only the environmental aspects have an impact. Meanwhile, the other two economic and social aspects have stayed the same. Therefore, the results show that, in general, the welfare condition of the Tambaklorok community did not change after the development of the Tambaklorok Tourism Village in the first five years. Therefore, it needs further action. Keywords: environmental, home-based enterprises, slum, socio-economic, sustainable settlement